2018
DOI: 10.1111/jdv.14931
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine patterns in vitro, in particular IL‐5/IL‐8 ratio, to detect patients with nickel contact allergy

Abstract: Assessment of the ratio of Ni-induced IL-5 and reduced IL-8 production in vitro is a helpful tool for a better characterization of Ni-allergic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 42 publications
3
30
3
Order By: Relevance
“…However, no significant differences between allogenic or autologous serum were reported in a MELISA test study 27 . Despite the discrepancies among these reports, which might be due to a high level of variability between human serum lots, the use of autologous serum seems to be on the rise, 28‐30 which is strongly supported by our results.…”
Section: Discussionsupporting
confidence: 91%
“…However, no significant differences between allogenic or autologous serum were reported in a MELISA test study 27 . Despite the discrepancies among these reports, which might be due to a high level of variability between human serum lots, the use of autologous serum seems to be on the rise, 28‐30 which is strongly supported by our results.…”
Section: Discussionsupporting
confidence: 91%
“…Given the level of sensitivity, the number of false negatives, and interlaboratory variation, the lymphocyte transformation test seems very unlikely to be a replacement for patch testing, but does have the advantages that additional endpoints such as the identity of the proliferating cells (CD4 or CD8) or the nature of cytokine production can be incorporated to improve mechanistic understanding. 7,47,48 In addition to sensitization being associated with changes in the profile of naïve and effector/central memory and EMRA cells, we also observed that, particularly for extremely allergic individuals, the Treg frequency was decreased, as was the CD4 + /CD8 hi ratio, whereas CLA expression was increased. These findings appeared to be a feature of sensitization to each of the three different allergens, despite the fact that they have very different chemistries.…”
Section: Discussionmentioning
confidence: 58%
“…45 The reasons for this lower share of positivity in our study are not clear, although it is noted that minor technical differences in the lymphocyte transformation test protocol can have marked effects, such as the use of autologous serum, 46 or the length of time in culture (5 days vs 6 or 7 days). 39,40,47 The lowest number of responders (5/12) was recorded for the extremely (+++) sensitized group, although mean proliferation was similar between the ++ and + ++ groups. This inverse dose-response relationship may indicate that the culture conditions were not optimal, rather than a true negative correlation of proliferation with patch test sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…IL‐8, which is usually upregulated in in vitro evaluation of the sensitizing potential of chemicals in dendritic and THP‐1 cells, was inhibited by nickel in this test. Therefore, Summers et al . calculated the IL‐5/IL‐8 ratio, a measure which slightly increased the sensitivity of the in vitro test, but at the expense of a reduced specificity.…”
mentioning
confidence: 99%
“…IL-8, which is usually upregulated in in vitro evaluation of the sensitizing potential of chemicals in dendritic and THP-1 cells, was inhibited by nickel in this test. Therefore, Summers et al 4 calculated the IL-5/IL-8 ratio, a measure which slightly increased the sensitivity of the in vitro test, but at the expense of a reduced specificity. This is not yet the definite answer to resolve the limitations of in vitro testing in the diagnosis of contact allergy, but the combination of different in vitro techniques with inclusion of measurement of T-cell cytokines may be an important aspect to explore, as observed in non-immediate drug eruptions.…”
mentioning
confidence: 99%